Report of 21st general assembly - ASEAN Inter-parliamentary organization - Asean inter- parliamentary assembly, Hội đồng liên nghị viện ASEAN (ASEAN Inter - Parliamentary Assembly (AIPA), 2000)
Hội nghị lần thứ 21 của Tổ chức liên nghị viện ASEAN đã được tổ chức tại Singapore từ ngày 10-15 tháng 9 năm 2000.